Using experiment to help understanding valuation issues / Ting Kien Hwa, Rohayu Abdul Majid and Suriyana Mustafar - Ting, Kien Hwa; Abdul Majid, Rohayu; Mustafar, Suriyana (UiTM Press, 2020)
Traditional teaching method using lectures are unable to relate to real property valuation processes. Recent explorations of the experimental method have lead to its applications into the field of real estate. Experimental method utilize experiments and demonstrations to simulate real estate processes to examine various theories and hypotheses. The design of an experimental method involves: 1. Determine the learning outcome, 2. Design the experiment, 3. Implementation, 4. Statistical test and results. The main part of the study took place during three class days with the students divided into two groups. The Expeimental (EXP) Group is subject to observing a demonstration whereas the Control Group (CON) attend the normal lectures. The test scores are analysed using mean score of EXP and CON groups and mean difference analysis using ANOVA analysis. The ANOVA shows significant differences between the two groups of students in understanding valuation smoothing. The group that has undergone experiments is found to have a higher score in the test and shows better understanding towards the smoothing processes. Significant statistical difference in mean test values implies the success of the application. The experimental method is found to improve understanding theoretical principles and improve problem solving skills. Upon successful validation of the method, it can be applied to other similar topics/issues in the same subject or other subjects. Thus widening the teaching delivery options in the classroom other than lectures, tutorials, case studies etc.